2022
DOI: 10.3390/cancers14205046
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Blockade: A Strategy to Unleash the Potential of Natural Killer Cells in the Anti-Cancer Therapy

Abstract: Immune checkpoint inhibitors (ICIs) immunotherapy has represented a breakthrough in cancer treatment. Clinical use of ICIs has shown an acceptable safety profile and promising antitumor activity. Nevertheless, some patients do not obtain clinical benefits after ICIs therapy. In order to improve and cure an increasing number of patients, the field has moved toward the discovery of new ICIs expressed by cells of innate immunity with an elevated inherent antitumor activity, such as natural killer cells. This revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 107 publications
0
7
0
Order By: Relevance
“…The results showed that the proportion of Tregs in the mice treated with ES@CuO+PD‐1 was significantly lower than that in the control mice, while the proportion of CD3 + CD4 + T cells did not change among the groups (Figure S20 , Supporting Information). Natural killer (NK) cells are a subset of lymphocytes responsible for antitumor activity; [ 39 , 40 ] therefore, tumor‐infiltrating NK cells were also analyzed. The results demonstrated that more NK cells infiltrated the TME after treatment with ES@CuO+PD‐1 therapy (Figure 6F,G ).…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the proportion of Tregs in the mice treated with ES@CuO+PD‐1 was significantly lower than that in the control mice, while the proportion of CD3 + CD4 + T cells did not change among the groups (Figure S20 , Supporting Information). Natural killer (NK) cells are a subset of lymphocytes responsible for antitumor activity; [ 39 , 40 ] therefore, tumor‐infiltrating NK cells were also analyzed. The results demonstrated that more NK cells infiltrated the TME after treatment with ES@CuO+PD‐1 therapy (Figure 6F,G ).…”
Section: Resultsmentioning
confidence: 99%
“…CD56 bright NK cells are considered efficient cytokine producers and are the main NK cell population infiltrating cancer tissues, while the CD56 dim NK cell subset (the most mature and 90% of peripheral blood NK cells) is able to mediate a strong cytotoxic response upon the engagement of activating receptors and even to exert antibody-dependent cellmediated cytotoxicity (ADCC) [36]. Among NK cells, we detected that both CD56 dim NK and CD56 bright NK were higher in patients with DC compared to patients with PD.…”
Section: Discussionmentioning
confidence: 99%
“…A study found that the infusion of allogeneic donor NK cells in 15 patients with NSCLC led to partial tumor shrinkage in two patients and stable disease in six patients 27 . In NSCLC patients with nivolumab treatment, higher absolute numbers of circulating NK cells were associated with longer OS 28 . Several human studies have demonstrated that PD‐1 expression on NK cells is present in cancer patients and weakens their antitumor effects.…”
Section: Discussionmentioning
confidence: 99%
“… 27 In NSCLC patients with nivolumab treatment, higher absolute numbers of circulating NK cells were associated with longer OS. 28 Several human studies have demonstrated that PD‐1 expression on NK cells is present in cancer patients and weakens their antitumor effects. However, the use of immune checkpoint inhibitors can enhance the effect of NK cells.…”
Section: Discussionmentioning
confidence: 99%